Presentation and Management of Parathyroid Tumors - Wajahat Hussain Wasty; Khalid Hussain Mahida; Khalid Iqbal (ziauddin University, 2024)
Objective: To evaluate cases presenting with parathyroid tumors and the efficacy of treatments offered. Methods: Six cases presented with bony manifestations in mandible, femur, tibia and maxilla while one presented with an overt neck swelling. Renal calculi showed in one case. All cases were subjected to assessment of serum parathyroid hormone level and radionuleotide scan.Sonography was done in addition in two of the cases . In all cases parathyroid tumors were identified and subjected to exploratory parathyroid surgery, In addition bony pathologies were subjected to excisions of the lesions. Results: In all the cases serum parathyroid hormone levels were raised.MIBI scans picked parathyroid tumors in almost all the cases. Six of the excised tumors were parathyroid adenomas while one was adenocarcinoma. Additional surgeries done in these cases include excisions of mandibular growths, maxillectomy and osteotomies on tibia and femur. All were giant cell tumours.One case with adenocarcinoma expired. The other cases showed normalization of parathyroid hormone levels. Conclusion: Parathyroid adenoma is the common benign tumor of parathyroid gland usually presenting with exaggerated parathyroid hormone levels. Ultrasound scan screening with tc99 Sestamibi scanning are most helpful in establishing the diagnosis. Parathyroid surgery is safe in experienced hands and is the standard treatment modality to reverse the morbidity associated with pathologies. In all bony lesions with a doubtful clinical diagnosis screening for Parathyroid lesions is mandatory. Gross disfigurements, functional disabilities call for excision of bony lesions. Key Words: Parathyroid Gland, Adenoma, Gaint Cell Tumour, Sestamibi Scan.